The Effect of Transformational Leadership and Competence on Organizational Citizenship Behavior (OCB) - Dakikotis Sururiyah (Syntax Literate, 2023)
This study aims to analyze how organizational citizenship behavior (OCB) is affected by transformational leadership (TL) and competence (CO). The sample of this research is 44 employees at the PT X Units Y. This research uses a multiple regression test. The result showed that transformational leadership (TL) and competence (CO) has a positive significant influence on Organizational Citizenship Behavior (OCB) and also together affect Organizational Citizenship Behavior (OCB). For managerial implications, human competence could be optimized by several programs like reward and recognition programs for inspiring employees PT. X.